An efficient two-level image encryption system using chaotic maps. (23rd May 2023) - Patro, K. Abhimanyu Kumar; Acharya, Bibhudendra
This paper proposes an image securing technique that aims to provide two-level security on two images in terms of encryption at the same time. In this technique, both bit and pixel-level encryptions are carried out; first, the pixel-level-shuffling is performed using the piece-wise linear chaotic map (PWLCM); then, the diffusion in bit-level is performed using the key-image. The bit-level diffusion using chaos not just to confuse the pixels, but is also diffuses them intensely. In addition, the bit and pixel-level processes improve that algorithm's security. Additionally, the parallel bit-plane diffusion process reduces the method's computational complexity. This technique uses one type of one-dimensional chaotic map in both permutation and diffusion, thereby increasing the algorithm's hardware and software efficiency. The results of the security analysis and simulation show that the suggested method is more effective in encoding and improves the security of the encrypted images.